PEMBINAAN NARAPIDANA ANAK DI LEMBAGA PEMASYARAKATAN KELAS 2 B PADANGSIDIMPUAN - Nurhamidah Gajah (Universitas Muhammadiyah Tapanuli Selatan, 2017)
The purpose of this research was to find out the founding of Child Prisoner in Class 2B of Prison in Padangsidimpuan, and the constraint and solution of the jailer to the child prisoner. The method used was descriptive method with analysis approach qualitative descriptive while the technique of the collecting data through observation, interview, and document analysis. Moreover, the result of this research can be concluded that the founding of Child Prisoner in Class 2B of Prison in Padangsidimpuan is still far from the expectation, it showed from 2 programs in class 2B of LAPAS Padangsidimpuan that were not running well. There was some founding that were not executed successfully for child prisoner such as the self management and behavioral founding. They only have religion founding. The constraints of the founding are the lack of facility to support the founding program and also the lack of official to guide the prisoner. To solve the problem, LAPAS start to build the facility and renovate the whole infrastructure of Class 2B Lapas Padangsidimpuan and make some agreements with Satpol PP Padangsidimpuan to back up the lack of the official in Lapas Padangsidimpuan.